الضغوط النفسية لدى مربي التربية الخاصة في ظل جائحة كورونا - خلفاوي، أميرة (جامعة الوادي university of Eloued, 2021)
الملخص: مــلــخــص الــدراســة بالعربية هدفت الدراسة الحالية للكشف عن مستوى الضغوط النفسية لدى مربي التربية الخاصة في ظل جائحة كورونا، اعتمدنا على المنهج الوصفي التحليلي،واستخدمنا مقياس الضغوط النفسية لدى مربي التربية الخاصة في ظل جائحة كورونا، كما تم اختيار عينة الدراسة بطريقة عشوائية والتي بلغت 45 مربي ومربية من ولاية الوادي، وقمنا بتحليل البيانات بواسطة الرزمة الإحصائية للعلوم الاجتماعية SPSSوأسفرت على النتائج التالية: - مستوى الضغوط النفسية لدى مربي التربية الخاصة في ظل جائحة كورونا متوسط. - لا توجد فروق ذات دلالة إحصائية في الضغوط النفسية لدى مربي التربية الخاصة في ظل جائحة كورونا تعزى لمتغير الجنس. - توجد فروق ذات دلالة إحصائية في الضغوط النفسية لدى مربي التربية الخاصة في ظل جائحة كورونا تعزى لمتغير الخبرة المهنية لصالح ذوي خبرة أقل من 05 سنوات. - لا توجد فروق ذات دلالة إحصائية في الضغوط النفسية لدى مربي التربية الخاصة في ظل جائحة كورونا تعزى لمتغير الحالة الاجتماعية. كلمات المفتاحية: الضغوط النفسية، مربي تربية الخاصة، جائحة كورونا. Résumé :فرنسية أو انجلزية The current study aims to detect the level of psychological stress in private educators under the Corona pandemic, we relied on the descriptive analytical approach, we used the measure of psychological stress among private educators under the Corona pandemic,the sample was chosen in a random way,the appropriate number of samples of 45 educators and from the El oued State,we also relied on the SPSS statistical package to analyze data that resulted in the following results: - The level of psychological stress among private educators under the Corona pandemic is medium. - There are no statistically significant differences in psychological stress among private educators under the CORONA pandemic due to the gendervariable. - There are statistically significant differences in psychological stress among special education educators under the Corona pandemic due to the variable in professional experience for those with less than 05 years of experience. - There are no statistically significant differences in psychological stress among private educators in the context of the Corona pandemic due to the changing social situation. Keywords: Psychological stress, private educator, Corona pandemic.
مذكرة ماستر علم الاجتماع تخصص تربية خاصة
Keywords: الضغوط النفسية، ذوي الإحتياجات الخاصة، جائحة كورونا; Stress psychologique, personnes ayant des besoins spéciaux, pandémie de Corona; Psychological stress, people with special needs, Corona pandemic